Tahap pengetahuan kaunselor pelatih terhadap etika kaunseling - Nurul Hasyimah, Mat Rani (Universiti Malaysia Sarawak, UNIMAS, 2006)
The objective of this study is to determine the level of knowledge of trainee counse l lor s towards counse l ling ethics in Universiti M alay sia Sarawak (UNIMAS). The ethical a spects included in this paper are confidentiality, informed consent and dual relationship. T his study is also carried out to determine the difference bet ween demography factors (ethnic and year of study) on counse l lin g ethics . Th is is a quantitative study carried out using survey method. Questionnaires we re given to all trainee counse l lor s in UNIMAS who have taken counse l ling ethics course. The total number of student s taking this course is 122. T he questionnaire is d ivided into three parts, part A: respondent background, part B: counse lling ethics and part C: e thical aspect s and function s that are important in counse l ling profession. Statistical method use d in this study is descriptive statistics, inferency statistic s (t - test and Oneway ANOVA) and level of knowledge in counse lling ethics. Result after sur vey shows that trainee counse llor s ’ level of knowledge in counse l ling e th ics in UNIMAS is high. There is no difference be tween demography factor (ethnic ) with trainee counse l lor s ’ level of knowledge towards ethics in confidentiality, informed consent and dual relationsh ip. The re are also no difference between demography factor ( year of study ) with confidentiality an d informed consent but there is a difference between y ear of study and dual relationship.